Cervical Cystic Lymphangioma, Rarely Detected in Adults with Rapid Progression, 2 Case Reports (Bangladesh Journal of Medical Science, 2023)
Cystic Lymphangioma(CL) is rarely detected in adulthood. We presented two cases with neck swelling at an advanced age. Both of cysts were located in the cervico-mediastinally and showed rapid progression. The cysts were excised successfully and there was no recurrence in the follow-up period. Although there are many alternatives in treatment, CL, which is rare in adults, can be treated with surgical excision successfully in appropriate cases to definitively prevent recurrence and complications.Bangladesh Journal of Medical Science Vol. 22 No. 03 July’23 Page : 709-711